Adolescents Who Vape Nicotine and Their Experiences Vaping: A Qualitative Study - Catherine E Dubé; Lori Pbert; Catherine S Nagawa; Dante P Simone; Jessica G Wijesundara; Rajani S Sadasivam (SAGE Publishing, 2023)
Introduction: Understanding adolescent perceptions of vaping and roles it plays in their lives is needed to design effective interventions to help adolescents quit. We explored vaping experiences of 11 adolescents from initiation through quit attempts. Methods: A convenience sample of students who vaped in the last 90 days was recruited from one suburban high school in Massachusetts. Qualitative interviews were transcribed and coded. An inductive thematic analysis approach was employed. Areas of agreement and range of responses in code reports were summarized. Results: Eleven open-ended semi-structured interviews were conducted (mean = 32.5 minutes each). Vaping initiation often occurred when socializing with friends who also supplied vaping devices. Vaping was "something to do" and new flavors engaged adolescents further. Solitary activities coupled with vaping included video gaming, getting ready for school, talking on the phone, or studying. Peak hours for vaping included morning, before and after school, before parents returned from work, and after parents went to bed. Several vaped to address anxiety/stress. For some, anxiety control was a main reason for vaping. Participants were concerned about health effects and nicotine dependence. Cost and health effects were drivers of quitting. Quit strategies relied on willpower and distraction. Conclusions: Peers have powerful influences on the initiation and maintenance of adolescent vaping. Vaping habits can become routinized into adolescent lives. Addiction is a concern although nicotine's anxiolytic effects were valued by many. Social connection was enhanced by communal vaping, sharing, and common vernacular, secrecy and rule-breaking. We describe the context in which adolescents vape nicotine, their reasons for vaping, and reasons to quit. This information can inform the development of interventions to better address adolescents' triggers to vape, and social and psychosocial barriers to quitting. Our findings suggest a desire to quit vaping but a limited awareness of quitting strategies.